Transcription factor NF-κB unravels nucleosomes - Stormberg, Tommy; Filliaux, Shaun; Baughman, Hannah E.R.; Komives, Elizabeth A.; Lyubchenko, Yuri L. (Biochimica et biophysica acta. General subjects, 2021)
NF-κB is a transcription factor responsible for activating hundreds of genes in mammalian organisms. To accomplish its function, NF-κB must interact with DNA occupied by nucleosomes, but how this interaction occurs is unclear. Here we used Atomic Force Microscopy to characterize complexes of NF-κB with nucleosomes assembled on different DNA templates. The assembly of NF-κB-nucleosome complexes leads to a substantial decrease of DNA wrapping efficiency from 149 ± 2 bp (SEM) for the control nucleosome sample to 135 ± 3 bp for complexes of nucleosomes with NF-κB. Mapping of the nucleosomes did not reveal displacement of under-wrapped nucleosomes from their original position, suggesting that unravelling involves dissociation of one or both flanks of the nucleosomes. Binding of NF-κB to the core was identified by nucleosome core volume measurements. We discovered two binding modes of NF-κB associated with nucleosome unravelling - NF-κB bound to the nucleosome core and to the DNA flanks. From these findings we propose two models explaining the interaction of NF-κB with the nucleosome complex. The partial unravelling of nucleosomes by NF-κB makes the DNA segment at the edge of the nucleosome core accessible, facilitating the transcription process. We speculate that NF-κB can function as a pioneer factor, enhancing its ability to facilitate rapid transcriptional response to cell stress. [Display omitted] •Interaction of transcription factor NF-κB nucleosomes was visualized with AFM.•NF-κB binds nucleosomes resulting in unwrapping of the nucleosome.•NF-κB is capable to unwrap almost a quarter of the DNA turn around the nucleosome core.•Transcription factor NF-κB has a dual function acting also as a pioneer factor.